Effects of eCG or estradiol benzoate administration associated with PGF2a on fertility of early weaned hereford cows in poor body condition - Fernández Abella, D.; Villegas, N. (Agrociencia Uruguay, 2002)
In order to evaluate the effect of hormonal treatments of fertility of early weaned beef cows, an experiment was carried out in a commercial cattle farm. 181 Hereford multiparous cows were allotted according to body weight and the same body condition (BC= 3, score 1 to 8), in three similar groups. 28 days after weaning the treatments were assigned: T1 - an im dose of PGF2a repeated on the 12th day plus estradiol benzoate (EB) on day 13 (n=50); T2- an im dose of PF2alfa repeated on the 12th day plus 400 I.U. of equine corionic gonadotropin (eCG), with the second dose of PGF2a (n=50) and T3- control group (without hormonal treatments; n=81). The cows were insemined with frozen semen from the same bull, at the fixed time (60-66 hours after the end of treatment) in the treatments T1 and T2, and 12 hours after the detection of estrus in the control group (T3). The ovarian activity dosage was determined through plasma progesterone concentration on day 8 post-insemination. Pregnancy was determined 60 days post-insemination by rectal examination. Treatment T1 induced and synchronized estrus in a greater number of animals 76.0 and 62.0% in T1 and T2, respectively. The conception rate was greater in the treated than in the control animals, especially when eCG was used 42,0; 62,0 24,7% for animals in T1, T2 and T3, respectively (P< 0.05). The conception rate in weaned cowes with poor body condition score (CC=3)can be improved by hormonal treatments.